STRATEGI PEMANFAATAN LIMBAH PERTANIAN UNTUK PENINGKATAN NILAI EKONOMI DAN LINGKUNGAN DI KABUPATEN CILACAP - Maghfuri, Ahamd (Badan Perencanaan Pembangunan Penelitian dan Pengembangan Daerah Kabupaten Cilacap, 2023)
Agricultural waste is material discarded from the agricultural sector that can still be utilized. Utilization of the leftover waste from agricultural activities can increase economic and environmental value. The large amount of agricultural waste from the results of agricultural activities is a great opportunity for the utilization of agricultural waste to support economic growth and environmental sustainability. Therefore, this study was conducted to determine strategies for utilizing agricultural waste. The research method used was descriptive qualitative with the research object being agricultural waste in Cilacap Regency using SWOT analysis which was carried out to find strategies by looking at strengths, weaknesses, opportunities, and threats in terms of agricultural waste utilization. The study resulted in Agricultural Waste Utilization Strategies being divided into three types of strategies based on their implementation period: long-term, medium-term, and short-term. The long-term strategy is the development of agricultural waste management areas, the medium-term strategy includes giving agricultural waste management tools to farming communities, and the short-term strategy is the first step in planning with outreach and training. The research is expected to be applied to increase the economic value of managed agricultural waste and improve environmental sustainability in harmony with sustainable development in Cilacap Regency.